Objeción de conciencia y nuevo protocolo del Ministerio de Salud - García P., Gonzalo; Valenzuela P., Sergio (Revista Hospital Clínico Universidad de Chile, 2017)
The beginning of the implementation at the institutional level of Law 21.030, relating to the decriminalization of pregnancy for three reasons, has generated concerns, practical difficulties and changes in the dynamics of work teams in hospitals that have had to implementar. These difficulties refer to areas as varied as diagnosis, confirmation of the causes, to the opposition of different professionals in their participation in the process. In this first communication we will summarize the last of the problems arising from the new protocol issued by the Ministry of Health, regarding the Institutional Awareness Objection in Hospitals that, like the HCUCH, have an agreement with FONASA.